2014
DOI: 10.1007/s12602-014-9164-4
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Properties of Lactobacillus crispatus 2,029: Homeostatic Interaction with Cervicovaginal Epithelial Cells and Antagonistic Activity to Genitourinary Pathogens

Abstract: Lactobacillus crispatus 2029 isolated upon investigation of vaginal lactobacilli of healthy women of reproductive age was selected as a probiotic candidate. The aim of the present study was elucidation of the role of L. crispatus 2029 in resistance of the female reproductive tract to genitourinary pathogens using cervicovaginal epithelial model. Lactobacillus crispatus 2029 has surface layers (S-layers), which completely surround cells as the outermost component of their envelope. S-layers are responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 58 publications
5
39
0
1
Order By: Relevance
“…A continuous production of IL-8 promotes, for instance, the infiltration of neutrophils, which are not only inefficient in resolving Chlamydial infections but can also release proteases that may damage surrounding cells (Skwor et al, 2008). In agreement with several studies (Abramov et al, 2014;Zaga et al, 2004), our results showed that L. crispatus and its culture supernatant decreased IL-6, IL-8 and TNF-␣ production in C. trachomatis-infected HeLa and J774 cells. Our data suggest that Lc and CSLc trigger the host innate immune response and reduce the production of pro-inflammatory cytokines in the presence of C. trachomatis infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A continuous production of IL-8 promotes, for instance, the infiltration of neutrophils, which are not only inefficient in resolving Chlamydial infections but can also release proteases that may damage surrounding cells (Skwor et al, 2008). In agreement with several studies (Abramov et al, 2014;Zaga et al, 2004), our results showed that L. crispatus and its culture supernatant decreased IL-6, IL-8 and TNF-␣ production in C. trachomatis-infected HeLa and J774 cells. Our data suggest that Lc and CSLc trigger the host innate immune response and reduce the production of pro-inflammatory cytokines in the presence of C. trachomatis infection.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported to promote the stability of the normal vaginal microbiota while its absence has been associated with a range of vaginal abnormalities (Macklaim et al, 2013;Fredricks et al, 2007). L. crispatus can inhibit the growth of pathogens such as Escherichia coli, Proteus vulgaris, Enterococcus faecalis, Streptococcus agalactiae and Staphylococcus aureus, probably due to the production of lactic acid (Abramov et al, 2014). Lactobacilli can inhibit chlamydial infection through multiple mechanisms, of which lactic acid-mediated C. trachomatis killing is clearly the most efficient (Gong et al, 2014), but the exact inhibition mechanism on the C. trachomatis pathogenetic effect by the Lactobacillus strains has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The amounts of H 2 O 2 produced by the Lactobacillus strains were similar to those observed in other studies analysing probiotic properties of vaginal lactobacilli isolated from healthy women (Abramov et al, 2014). The production of H 2 O 2 by lactobacilli is one of the most important defense mechanisms against colonization by pathogenic or opportunistic microorganisms (Dover et al, 2008).…”
Section: Hydrogen Peroxide and Lactic Acid Productionsupporting
confidence: 84%
“…The capability of different Lactobacillus species to increase the immunological response has also been reported in fish such as sea bass [67] and gilthead seabream [70]. In addition, specimens of Senegalese sole farmed under high stocking density and receiving a diet supplemented with SpPdp11 showed a higher resistance to disease in comparison with fish fed the diet without the probiotic [67], and this higher resistance was related to important changes in the intestinal microbiota, such as the presence of L. fermentum only in fish fed the diet supplemented with the probiotic [43].…”
Section: Discussionmentioning
confidence: 82%